Experimental assessment of the flexural behaviour of circular rubberized concrete-filled steel tubes. (July 2016) - Silva, A.; Jiang, Y.; Castro, J.M.; Silvestre, N.; Monteiro, R.
Abstract: The main objective of the research presented in this paper is to investigate the flexural behaviour of concrete filled steel tube (CFST) columns of circular cross-section, made with rubberized concrete (RuC). A second objective is to identify behavioural differences between this type of composite members and typical CFST members made with standard concrete (StdC), namely in terms of the influence of the rubber aggregate replacement ratio on member strength, ductility, and energy dissipation capacity. The paper describes the preparation and development of an experimental campaign, involving the testing of 16 circular specimens, 12 RuCFST and 4 StdCFST. The definition of the test campaign considered a number of parameters, namely cross-section slenderness, aggregate replacement ratio, axial load level and loading type. A special device was developed as part of an innovative testing setup, aimed at reducing both the cost and preparation time of the specimens. This paper also describes the comparison of the test results with design provisions from Eurocode 4. The test results show a marginal influence of the type of concrete infill on the monotonic and cyclic behaviour of the members and also allow concluding that Eurocode 4 is conservative in predicting the capacity of the tested specimens. Moreover, it is found that the cross-section slenderness does not have a significant influence on the monotonic and cyclic behaviour of the specimens, pointing out for the possible relaxation of the cross-section slenderness limits currently specified in Eurocodes 4 and 8. Highlights: The flexural behaviour of Concrete Filled Steel Tube is investigated. A comparison is made between the test results with the design provisions from Eurocode 4. Marginal influence of the type of concrete infill on the monotonic and cyclic behaviour Eurocode 4 is conservative in predicting the flexural capacity of circular CFST. Cross-section slenderness does not have a significant influence on the monotonic and cyclic behaviour.